Analysis of Cross-Border Cash Carrying (CBCC) Threat Countermeasures From A Customs and Strategic Intelligence Perspective - Aditya Rachman Rony Putra; Arthur Josias Simon Runturambi (Journal Research of Social Science, Economics, and Management, 2023)
This research departs from the problem of potential losses in Indonesia stemming from the actions of Cross Border Cash Carrying (CBCC). In 2018 it was estimated that there were 12 trillion rupiah suspected of entering Indonesia unreported and suspected to be a criminal practice of money laundering (TPPU) and financing of terrorism activities. To that end, this article aims to provide an overview of how CBCC threat countermeasures from a strategic customs and intelligence perspective. Using a qualitative approach, this article analyzes the problem using descriptive methods. The data sources used are secondary data derived from open sources such as news articles, academic research journals and institutional documents related to the problem under study. The results showed that the CBCC threat in addition to having an impact on economic aspects is also strongly related to the threat of other transnational crimes such as narcotics trafficking and terrorism financing. Therefore, this CBCC threat cannot be underestimated and must get an appropriate approach to overcome it. From a customs and strategic intelligence standpoint, surveillance of CBCC practices requires a wealth of data from multiple points of view to provide comprehensive mapping of the problem. In addition, appropriate intelligence data exchange media is needed so as to enable every surveillance agency, especially the DGCA, to have easy access to any data needed for surveillance and enforcement. In addition, regulatory improvements and strengthening the legal foundation continue to be pursued to support the effectiveness of enforcement in the field.